Trichoscopy as a Simple Diagnostic Tool for Trichotillomania; An Observational Study - Fauzia Musbah,* Nadea Elhouni (AlQalam Journal of Medical and Applied Sciences, 2020)
Background and objective: Trichotillomania is a chronic illness characterized by hair bearing areas with patchy alopecia due to compulsive urge to pull the hair. Scalp is the most frequently affected area for pulling hair. Typically, patients may have only small areas of baldness, in severe cases, tonsure appearance of baldness is noticeable. This study aimed to observe trichoscopic patterns and their significance in the diagnosis of trichotillomania. Methods: An observational study conducted between march 2018 and march 2020 on 19 alopecic patients attending outpatient department in Tripoli central Hospital. Dermoscope was used to save the images of the affected alopecic patients. Results: In this current study, most of the patients belonged to adolescent, and child age group and most of them were females Most common symptom was black dots over the scalp (94.7%) followed by V shape (78.9%) and broken hair (73.6%). The lowest one was for coiled hair (15.7%). Conclusion: Trichoscopy techniques can be utilized in this condition, and help forming and confirming the diagnosis on the basis of its characteristics finding. Hence, trichoscopic assessment should be conducted in every case of alopecia.